Utilization of Bamboo Waste by Engineering Acid Hydrolysis (H2SO4) to Produce Furfural Compounds - Fitri, Nur Hidayatul; Ramandani, Adityas Agung; Cendekia, Devy; Teguh, Dedi (Universitas Ahmad Dahlan, 2023)
Bamboo waste containing lignocellulosic can be used as a material for forming furfural compounds. Furfural is an intermediate product that is widely needed by the chemical industry in the manufacture of finished products such as resins, disinfectants, lubricating oils, synthetic rubber, and so on. This product can be produced from materials containing pentosan. The purpose of this study was to determine the effect of the delignification process on pentosan levels,yield and characterization of the resulting furfural, as well as the potential of pentosan to become furfural compounds. In this study the formation of furfural from bamboo waste was carried out using the acid hydrolysis method, with the independent variables namely cooking temperatures of 90 oC, 100 oC and 110 oC, H2SO4 concentrations of 5%, 10% and 15% and cooking times of 60 minutes, 90 minutes , and 120 minutes. Based on the results of research that has been done, it is known that the delignification process has an influence on the pentosan level, where the sample without delignification obtained a pentosan level of 11.10% and using the delignification process obtained a pentosan level of 14.67%. Characterization of furfural analysis results by color test showed a change in color to red and based on the results of GC-MS analysis at retention time 24.